Produção e caracterização de amilases bacterianas: α-amilase e ciclodextrina glucanotransferase (CGTase) - Reis, Aline Aparecida dos [UNESP] (2015)
Together with other enzymes that degrade starch, α-amylases and CGTases are included in the family 13 glycosylhydrolases, characterized by a conformation (α/β)8-barrel. Amylases are an important group of industrial enzymes, accounting for approximately 25% of the world enzyme market. Bacterial strains from the Cerrado areas, which have shown a high production of amylase in the previous studies, have been isolated. Due to the interest in expanding the knowledge of α-amylase and CGTase with potential for industrial application, the present work proposes to conduct studies of physical and chemical analysis and the effect of carbon source on the production of α-amylase of A-1.2 and A-18 microbial strains, as well as CGTase produced by Paenibacillus campinasensis H69-3 in submerged fermentation using the soluble starch, wheat, corn, potato and cassava; wheat bran and cassava; Maizena and Arrozina like various alternative sources of carbon. Furthermore, it proposes enhancing the amylase study of the microbial strain A-1.2 by optimizing the nutritional components of the culture medium in which each of the factorial design experiments has been carried out in triplicate, and thus considering the average results of these repetitions. To initiate molecular biology studies with CGTase produced by P. campinasensis H69-3 searching strategies for the cloning and expression of the CGTase in a heterologous harbourer (E. coli). The A-1.2 and A-18 strains were the carbon sources of soluble, cassava and corn starch, and cassava bran as the substrate that maximized the enzyme production by both strains. And the fermentation time with higher levels of activity was between 72 and 96 hours. The production profile over the CGTase P. campinasensis H69-3 time has indicated the soluble and cassava starch and Maizena as carbon source that provided the highest enzymatic activities. The 72 hours period of time has been more appropriate in enzymatic tests, ...